Nanotoxicology: advances and pitfalls in research methodology. (September 2015) - Azhdarzadeh, Morteza; Saei, Amir Ata; Sharifi, Shahriar; Hajipour, Mohammad J; Alkilany, Alaaldin M; Sharifzadeh, Mohammad; Ramazani, Fatemeh; Laurent, Sophie; Mashaghi, Alireza; Mahmoudi, Morteza
As research progresses, nanoparticles (NPs) are becoming increasingly promising tools for medical diagnostics and therapeutics. Despite this rise, their potential risks to human health, together with environmental issues, has led to increasing concerns regarding their use. As such, a comprehensive understanding of the interactions that occur at the nano-bio interface is required in order to design safe, reliable and efficient NPs for biomedical applications. To this end, extensive studies have been dedicated to probing the factors that define various properties of the nano-bio interface. However, the literature remains unclear and contains conflicting reports on cytotoxicity and biological fates, even for seemingly identical NPs. This uncertainty reveals that we frequently fail to identify and control relevant parameters that unambiguously and reproducibly determine the toxicity of nanoparticles, both in vitro and in vivo . An effective understanding of the toxicological impact of NPs requires the consideration of relevant factors, including the temperature of the target tissue, plasma gradient, cell shape, interfacial effects and personalized protein corona. In this review, we discuss the factors that play a critical role in nano-bio interface processes and nanotoxicity. A proper combinatorial assessment of these factors substantially changes our insight into the cytotoxicity, distribution and biological fate of NPs.